RELATIONSHIP OF PORE NUMBER WITH CONSOLIDATION SETTLEMENT OF CLAY - Lola Cassiophea (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2014)
Settlement of the building can happen and will be happened, it is very detrimental to the stability of the building above the subgrade. The decrease can be considered stable when settlement has been predicted in advance by testing in the laboratory so that the building can be anticipated when settlement takes place. Consolidation is a process of downsizing volume slowly on perfectly saturated soil with low permeability due to partial drainage of pore water. Void ratio at the end of each period increase of pressure (load) can be calculated from the reading of the gauge dial and so is the case with moisture (water content) or dry weight (dry weight) of soil samples at the end of the test. All the land that is stressed will experience strain in the soil skeleton. Integration strain (deformation per unit length) along the depth of which is influenced by pressured is called voltage reduction. Tests conducted on water content, Atterberg tests, density test, grain size distribution and consolidation. Before the initial load is given shows that the initial compression is relatively large, but after a given initial load of 5 kPa, 10 kPa, 20 kPa, 40 kPa, 80 kPa produces variations of pore number with time of loading each one day, showed that the decline in the smaller clay consolidation, meaning the presence of a load that produces variations void ratio can reduce the compression clay. The ratio of the addition of a load of 40 kPa, 80 kPa on the graph void ratio and pressure of 5 kPa looks irregular, 10 kPa, 20 kPa. This is because at 10 kPa and 20 kPa has reached the maximum so that the additional load reduction that results in void ratio variations will not affect the decrease, thus the ratio of the addition of a load that produces a good variation of void ratio is at 10 kPa and 20 kPa